Considerations for dermatologists when treating U.S. Military Service Members - C.G. Kels, JD; L.H. Kels, MD, MPH (Wolters Kluwer, 2017)
Civilian dermatologists sometimes provide care to military service members. This article provides an overview of special considerations that are relevant to the dermatologic treatment of members of the U.S. Armed Forces. We provide a review of the potential implications of certain conditions and treatments for medical retention standards and discuss how service-connected disabilities due to skin conditions are rated and compensated. Understanding service members' circumstances and priorities can help guide discussions and decisions about their care.